Diabetes mellitus impacts on expression of DNA mismatch repair protein PMS2 and tumor microenvironment in pancreatic ductal adenocarcinoma. Issue 1 (1st December 2022) - Pan, Xuekai; Mizukami, Hiroki; Hara, Yutaro; Yamada, Takahiro; Yamazaki, Keisuke; Kudoh, Kazuhiro; Takeuchi, Yuki; Sasaki, Takanori; Kushibiki, Hanae; Igawa, Akiko; Hakamada, Kenichi
ABSTRACT: Aims/Introduction: The mismatch repair (MMR) protein recognizes DNA replication errors and plays an important role in tumorigenesis, including pancreatic ductal adenocarcinoma (PDAC). Although PMS2, a MMR protein, is degraded under oxidative stress, the effects of diabetes are still unclear. Herein, we focused on whether diabetes affected MMR protein expression in PDAC. Materials and Methods: Tissues from 61 surgically resected PDAC subjects were clinicopathologically analyzed. Immunohistochemical analysis was performed for MMR protein expression, oxidative stress, and immune cell infiltration. The change of MMR protein expression was assessed in PDAC cell lines under stimulation with 25 mM glucose and 500 μM palmitic acid. Survival curves were analyzed by the Kaplan–Meier method with the log‐rank test. Results: Diabetes complicated with dyslipidemia significantly decreased the expression of PMS2 in PDAC tissues with an inverse correlation with the degree of oxidative stress. Palmitic acid combined with high glucose induced degradation of PMS2 protein, enhancing oxidative stress in vitro . CD8 + T‐cell infiltration was associated with a short duration of type 2 diabetes (≤4 years) and a low expression of PMS2 in PDAC tissues, while CD163 + tumor‐associated macrophage infiltration was increased with a long duration of diabetes (>4 years). A short duration of diabetes exhibited a better prognosis than nondiabetic subjects with PDAC ( P < 0.05), while a long duration of diabetes had a worse prognosis ( P < 0.05). Conclusions: The different phases of diabetes have a major impact on PDAC by altering PMS2 expression and the tumor immune microenvironment, which can be targeted by an immune checkpoint inhibitor. Abstract : Diabetes Mellitus complicated with dyslipidemia generated high level of oxidative stress, resulting in the significant decrease in the expression of PMS2 in PDAC cells. Abundant CD8 + T‐cell infiltration was associated with a short duration of diabetes mellitus (≤ 4 years) and low expression of PMS2, which would strengthen the satisfactory prognosis caused by low expression of PMS2. However, the presence of massive CD163 + TAMs with the prolongation of the course of diabetes mellitus (> 4 years) impaired the benefits of low expression of PMS2 and led to poor prognosis. CD8, cluster of differentiation 8; CD163, cluster of differentiation 163; PDAC, pancreatic ductal adenocarcinoma; PMS2, PMS1 Homolog 2; TAMs, tumor‐associated macrophages.